Artificial intelligence in STEM education : the paradigmatic shifts in research, education, and technology - Ouyan, Fan; Jiao, Pengcheng; McLaren, Bruce M.; Alavi, Amir H. (Boca Raton, FL : CRC Press, 2023)
"Artificial intelligence (AI) opens new opportunities for science, technology, engineering and mathematics (STEM) education. AI in education (AIED) has undergone several research, practice, and technological paradigmatic shifts in its brief history, which can be particularly observed in STEM education. The development of AI in STEM education has experienced significant shifting of the focuses during the last decade. In general, it has been reshaped to gradually emphasize the learner-centered, while weakening the teacher-directed instruction mode. This has led to a change between the three paradigms: leaner-receiver, learner-partner, learner-leader. Consequently, supporting AI frameworks have been significantly improved from intelligent tutoring systems (ITSs), exploratory learning environments (ELEs) to human-centered participatory (HCP) smart education. This book aims to track the paradigmatic shifts of AI in STEM education and intends to highlight the reasons behind these changes as well as explain how the AI techniques have been improved to ensure the efficiency of the shifts. AI in STEM Education is a must-read for researchers, engineers, educators and policy-makers who are interested in opportunities and challenges of this growing field"--
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence -- Educational applications; Science -- Study and teaching -- Technological innovations; EDUCATION / Higher; TECHNOLOGY / General